Enacting citizenship through participation in a technological society: a longitudinal three-year study among people with dementia in Sweden. Issue 2 (21st February 2023) - Gaber, Sophie Nadia; Nygård, Louise; Malinowsky, Camilla; Brorsson, Anna; Kottorp, Anders; Hedman, Annicka
Abstract: The role of Everyday Technology (ET) use is presented as subsidiary or neutral in policy for age- and dementia-friendly communities; and yet, research suggests that older people, especially those with dementia, experience increased challenges using ET in their everyday lives. Through the lens of micro-citizenship, the study aims to deepen the knowledge about how use of ET outside the home, including portable ETs, relates to participation in places visited within public space among people with dementia over time. Using a longitudinal study design, 35 people with dementia were recruited at baseline and followed over three years. Data were collected through semi-structured interviews using standardised questionnaires: the Participation in ACTivities and Places OUTside Home Questionnaire (ACT-OUT) and the Everyday Technology Use Questionnaire (ETUQ). Random intercept modelling and descriptive statistics were used to analyse the data. Throughout the three-year study, decreasing use of ET outside the home, including portable ETs, was associated with decreasing participation in places visited within public space, in a statistically significant way when controlling for age ( F = 7.59, p = 0.01). The findings indicate that facilitating access and use of ET outside the home, among people with dementia, should be integral to promoting and maintaining participation in age- and dementia-friendly communities.